Mitogen‐activated protein kinase signaling mediates opioid‐induced presynaptic NMDA receptor activation and analgesic tolerance. Issue 2 (10th December 2018) - Deng, Meichun; Chen, Shao‐Rui; Chen, Hong; Luo, Yi; Dong, Yingchun; Pan, Hui‐Lin
Abstract: Opioid‐induced hyperalgesia and analgesic tolerance can lead to dose escalation and inadequate pain treatment with μ‐opioid receptor agonists. Opioids cause tonic activation of glutamate NMDA receptors (NMDARs) at primary afferent terminals, increasing nociceptive input. However, the signaling mechanisms responsible for opioid‐induced activation of pre‐synaptic NMDARs in the spinal dorsal horn remain unclear. In this study, we determined the role of MAPK signaling in opioid‐induced pre‐synaptic NMDAR activation caused by chronic morphine administration. Whole‐cell recordings of excitatory post‐synaptic currents (EPSCs) were performed on dorsal horn neurons in rat spinal cord slices. Chronic morphine administration markedly increased the frequency of miniature EPSCs, increased the amplitude of monosynaptic EPSCs evoked from the dorsal root, and reduced the paired‐pulse ratio of evoked EPSCs. These changes were fully reversed by an NMDAR antagonist and normalized by inhibiting extracellular signal‐regulated kinase 1/2 (ERK1/2), p38, or c‐Jun N‐terminal kinase (JNK). Furthermore, intrathecal injection of a selective ERK1/2, p38, or JNK inhibitor blocked pain hypersensitivity induced by chronic morphine treatment. These inhibitors also similarly attenuated a reduction in morphine's analgesic effect in rats. In addition, co‐immunoprecipitation assays revealed that NMDARs formed a protein complex with ERK1/2, p38, and JNK in the spinal cord and that chronic morphine treatment increased physical interactions of NMDARs with these three MAPKs. Our findings suggest that opioid‐induced hyperalgesia and analgesic tolerance are mediated by tonic activation of pre‐synaptic NMDARs via three functionally interrelated MAPKs at the spinal cord level. Open science badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : Under the normal condition, NMDA receptors at the pre‐synaptic terminals in the spinal cord are not phosphorylated or functionally active. However, pre‐synaptic NMDA receptors in the spinal dorsal horn become tonically activated during chronic morphine treatment. Here, we found that chronic treatment with morphine increases the association of NMDA receptors with three MAPKs (ERK1/2, p38, and JNK) in the spinal cord. This increased interaction leads to NMDA receptor phosphorylation at pre‐synaptic terminals. As a result, pre‐synaptic NMDARs are endogenously activated to augment synaptic glutamate release to post‐synaptic neurons in the spinal dorsal horn to cause opioid‐induced hyperalgesia and analgesic tolerance. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/